"It's Going to be Different for Everyone": Negotiating Quality of Life and Care Priorities Within Care Convoys. (August 2022) - Burgess, Elisabeth O.; Kemp, Candace L.; Bender, Alexis A.
Objective: The overall goal of this analysis was to learn about residents' quality of life and quality of care in assisted living over time and from multiple viewpoints within support networks.Method: This grounded theory analysis examined qualitative data collected from 50 residents and 169 of their care network members followed over two consecutive 2-year periods in 8 diverse settings.Results: Quality involved a dynamic process of "negotiating priorities, " which refers to working out what is most important for residents' quality of life and care. Resident and care partner priorities were not always consistent or shared, in part because quality is personal, subjective, dynamic, and situational.Discussion: Communication and collaboration among formal and informal care partners are vital to residents' ability to age in place with a high quality of life and quality care.